HUBUNGAN KESIAPAN BELAJAR WARGA BELAJAR DENGAN HASIL BELAJARNYA DALAM MATA PELAJARAN SOSIOLOGI PADA PROGRAMPAKET C SKB LIMA PULUH KOTA - Indri Marvianis (Universitas Negeri Padang, 2014)
This research is based on the low learning outcomes of the students in studying sociology at program package C SKB Lima Puluh Kota. The aim of the research is to describe at relationship between the student’s readiness to learn and learn ing outcomes using correlational approach. Questionnaires with data analisys Percentase and Rank Order form are used to collect data. The result of the research showed that there was a significant relationship between student’s readiness to learn and the learning outcomes in studying Sociology at program package C SKB Lima Puluh Kota.